« L’implantation » comme construction de la présence palestinienne au Liban durant la tutelle syrienne (1989-2005) - Daniel Meier (Revue des Mondes Musulmans et de la Méditerranée)
This paper tries to highlight the following question : how did lebanese political elites formulated and built the Palestinian refugee presence in post-civil war Lebanon ? In order to give some answers, the author studies the settlement or « implantation » question – al-tawtîn. In a first part, he shows social conditions for the developing of a narrative space on this question due to the signing of Taïf Agreements firstly and secondly because of the evolution of the political context in the Middle East after the Oslo Agreements. In a second part, the author examines lebanese political statements on the Palestinian question during the nineties and the beginning of the 2000s. Three types of interpretation  of al-tawtîn are detailed showing how diverse and polysemic this notion seems to be. Regarding communalist statements of the main lebanese political actors and the syrian hegemony over Lebanon, he concludes that al-tawtîn works like a para-narrative.